2002
DOI: 10.2527/2002.80102619x
|View full text |Cite
|
Sign up to set email alerts
|

Brewers dried yeast as a source of mannan oligosaccharides for weanling pigs

Abstract: Brewers dried yeast, a source of mannan oligosaccharides (MOS), was assessed as an alternative to an antimicrobial agent (carbadox) for young pigs in two experiments. The yeast contained 5.2% MOS. Agglutination tests confirmed adsorption of several serovars of E. coli and Salmonella spp. onto the yeast product. In Exp. 1, seven replicates (five pigs per pen) of 22-d-old pigs were fed a nonmedicated basal diet or the basal diet with carbadox (55 mg/kg), yeast (3%), or a combination of 3% yeast and 2% citric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
117
4
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(144 citation statements)
references
References 25 publications
17
117
4
6
Order By: Relevance
“…Several studies demonstrated that some other yeast products (brewer's yeast cells, etc.) can affect the composition of intestinal microflora (Naughton et al 2001;White et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that some other yeast products (brewer's yeast cells, etc.) can affect the composition of intestinal microflora (Naughton et al 2001;White et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to carbadox, mannans failed to reduce the length of the period of hyperthermia observed after infection with S. enterica and did not promote growth (Burkey et al, 2004). Total levels of serum IgA, IgM and IgG were not modified by dietary mannan, in piglets challenged or not with an enterotoxigenic strain of E. coli K88 (White et al, 2002).…”
Section: Natural Alternatives To In-feed Antibioticsmentioning
confidence: 86%
“…The increased blood lymphocyte population among leucocytes in mannan-fed animals could be linked more to B than to T-cells. Indeed, 3% of brewer's yeast (which corresponds to a final level of 0.16% of mannan oligosaccharide) only tended to increase the piglet serum level of IgG when used alone, but substantially increased this level when fed with the acidifier, citric acid (White et al, 2002). Conversely, blood proportions of CD4 1 or CD8 1 lymphocytes are insensitive to mannan supplementation .…”
Section: Natural Alternatives To In-feed Antibioticsmentioning
confidence: 98%
“…Multiple studies have demonstrated the immunostimulant properties of yeasts, such as their ability to enhance non-specific immune activity [92]. That reaction can be related to β-glucans, nucleic acids as well as mannan oligosaccharides [93]. Brewer's yeast may serve as an excellent health promoter for fish culture as even when administered for relatively long periods is able to enhance immune responses as well as growth of various fish species, without causing immunosuppression [94,95].…”
Section: Yeast Treats For Animalsmentioning
confidence: 99%